"Is an accreditation seal worth the effort?": Observations of programme accreditations in Lappeenranta University of Technology, Finland. Issue 3 (1st July 2014) - Niemelä, Hanna; Okkola, Taija; Nurkka, Annikka; Kuisma, Mikko; Tuunila, Ritva
Abstract : Purpose: – The purpose of this paper is to present observations of a EUR-ACE accreditation process in a Finnish university. The study demonstrates the effects (benefits, effort and resources required) of accreditation as seen by the university management and teaching staff. Design/methodology/approach: – The material of the study was gathered by conducting an interview and questionnaire survey after the accreditation processes of six degree programmes at Lappeenranta University of Technology, Finland, in 2011. Findings: – Besides certain shared views, the survey reveals some differences in opinions between the university management and the teaching staff: The management at all levels of the university valued the significance of accreditations somewhat higher than the teaching staff. Most of the interviewees found that accreditations have had an important effect on the curriculum work and thereby on the development of teaching and education. However, the effects on single courses were considered less significant. Research limitations/implications: – The study focuses on one university with a limited number of responses and one accreditation agency only (ASIIN, Germany). Originality/value: – The engineering degree programmes were the first ones to obtain a EUR-ACE accreditation both in Finland and in the Nordic countries. Thus, the results have a novelty value for Nordic universities and stakeholders in the education sector.